Formation of the Conceptual Basis of State Support for Development of Social Enterprises in Ukraine - Dikan, Olena; Obruch, Hanna; Panchenko, Nataliia; Frolova, Natalia (International Journal of Engineering and Technology, 2018)
The article deals with the phenomenon of social entrepreneurship. The importance of social enterprises in solving social problems and ensuring economic development of the state are outlined. The ranking of countries is based on the level of favorable conditions for the functioning of social enterprises, among which the most favorable conditions are characterized by the USA. The peculiarities of the state policy in the sphere of social enterprise development in South Korea are investigated, which, according to this rating, occupies the leading position among the countries in terms of state support of social business entities. The present state of development of subjects of social entrepreneurship in Ukraine is considered, which allowed to determine the main problems of their functioning. The conceptual basis of state support for the development of social entrepreneurship in Ukraine is formed, which is based on the definition of legal, financial, institutional and informational and consulting tools for the growth of social enterprises. Socio-economic effects of realization of social initiatives are revealed.Â